Variation in the Abundance of Bees Across Distinct Montane Meadows - Jessica N Welch (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
Across different landscapes, plant abundance and richness change. Bee distributions may vary spatially or temporally in accordance with differences in floral diversity. I used a habitat-based approach to investigate the hypothesis that the abundance of bees in assemblages varied among three distinct meadow types: dry meadow, wet meadow-Veratrum, and wet meadow-Salix. Patterns of bee abundance were sampled using bee bowls and netting around Gothic, Colorado. I sampled four triplets of sites (each consisting of the three meadow types) every other week, between June 22 and August 26, 2009. In total, I caught 2,938 bees and identified each of them to family. I found that there was no significant difference in the abundance of bees across the three meadow types. Furthermore, I did not detect a difference in bee abundance within a family across the three meadow types, though there were significantly more bees of the family Apidae than either Colletidae or Megachilidae within wet meadow-Veratrum sites. There was no significant relationship between bee abundance and the mean flower abundance or rarefied richness at sites. Overall, I found no difference in bee abundance at different meadow types once divided into four sampling periods; however, bee abundance for the family Apidae depended on time and meadow type while bee abundance for the family Halictidae depended on time only. Additional experimentation over multiple years may be needed to reveal significant patterns. About 50 percent of the variation in bee abundance was accounted for by site, rarefied plant species richness, and daily rainfall. Bee distribution may also depend on nesting preference, or perhaps there are species level differences that this experiment was no able to detect.